Cosmological constraint precision of photometric and spectroscopic multi-probe surveys of China Space Station Telescope (CSST). Issue 1 (8th December 2022) - Miao, Haitao; Gong, Yan; Chen, Xuelei; Huang, Zhiqi; Li, Xiao-Dong; Zhan, Hu
ABSTRACT: As a Stage IV space-based telescope, the China Space Station Telescope ( CSST ) can perform photometric and spectroscopic surveys simultaneously to explore the Universe efficiently in extreme precision. In this work, we investigate several powerful CSST cosmological probes, including cosmic shear, galaxy–galaxy lensing, photometric and spectroscopic galaxy clustering, and number counts of galaxy clusters, and study the capability of these probes by forecasting the results of joint constraints on the cosmological parameters. By referring to real observational results, we generate mock data and estimate the measured errors based on CSST observational and instrumental designs. To study systematic effects on the results, we also consider a number of systematics in CSST photometric and spectroscopic surveys, such as the intrinsic alignment, shear calibration uncertainties, photometric redshift uncertainties, galaxy bias, non-linear effects, instrumental effects, etc. The Fisher matrix method is used to derive the constraint results on the cosmological and systematic parameters from individual or joint surveys. We find that the joint constraints achieved by including all these CSST cosmological probes can significantly improve the results from current observations by one order of magnitude at least, which gives Ωm and σ 8 <1 per cent accuracy and w 0 and wa <5 and 20 per cent accuracy, respectively. This indicates that CSST photometric and spectroscopic multi-probe surveys could provide powerful tools with which to explore the Universe and greatly improve the studies of relevant cosmological problems.